Evaluation of the Hybrid Tracer Indocyanine Green–99mTc-Nanocolloid for Sentinel Node Biopsy in Bladder Cancer—A Prospective Pilot Study. (18th September 2022) - Rietbergen, Daphne D.D.; van Gennep, Erik J.; KleinJan, Gijs H.; Donswijk, Maarten; Valdés Olmos, Renato A.; van Rhijn, Bas W.; van der Poel, Henk G.; van Leeuwen, Fijs W.B.
Abstract : Rationale: In muscle-invasive bladder cancer (MIBC), lymph node invasion has proven to be an independent predictor of disease recurrence and cancer-specific survival. We evaluated the feasibility of targeting the sentinel node (SN) for biopsy in MIBC patients using the hybrid tracer indocyanine green (ICG)– 99m Tc-nanocolloid for simultaneous radioguidance and fluorescence guidance. Methods: Twenty histologically confirmed cN0M0 MIBC patients (mean age, 63.3 years; range, 30–82 years), scheduled for radical cystectomy with SN biopsy and extended pelvic lymph node dissection (ePLND), were prospectively included. Twelve patients were operated on following neoadjuvant chemotherapy. The patients received lymphoscintigraphy as well as SPECT/CT after 4 transurethral injections of ICG- 99m Tc-nanocolloid (mean, 208 MBq; range, 172–229 MBq) around the tumor/scar in the detrusor muscle of the bladder on the day before radical cystectomy. Sentinel node resection was performed under radioguidance and fluorescence guidance. Results: Nineteen patients could be analyzed. On preoperative imaging, SNs could be identified in 10 patients (53%; mean, 1.6 SN/patient), which revealed drainage pathways outside the ePLND in 20% of the patients. Interesting to note is that 2 patients (10%) with preoperative nonvisualization displayed fluorescent and radioactive SNs during surgery. Location of the primary tumor near the left lateral side of the bladder seemed to be a factor for nonvisualization. Nodal harvesting with ePLND varied among patients (mean, 23.3). Histopathology confirmed tumor-positive nodes in 4 (21%) of all patients. In the 2 patients where an SN could be identified, the ePLND specimens were tumor-negative. All patients with tumor-positive nodes had advanced disease (stage III). Conclusion: Sentinel node biopsy in bladder cancer using the hybrid tracer ICG- 99m Tc-nanocolloid is feasible, and preoperative imaging is predictive for the ability to perform SN biopsy in 83% of the patients who displayed an SN. In patients with a successful preoperative SN mapping using lymphoscintigraphy and SPECT/CT, the intraoperative SN guidance and detection were effective, even outside the ePLND area. As such, this study underscores the critical role that preoperative imaging plays in challenging image-guided surgery applications.